7 - Mozambique: The Rise of a Micro Dual State: https://doi.org/10.4314/ad.v34i3-4.63532 - Meneses, Maria Paula; Santos, Boaventura de Sousa (Africa Development, 2009)
The decade from 1990 to 2000 was a period of sustained political activity in Africa, leading towards democratisation. Under this scope, Mozambique is widely seen as one paradigmatic success story. Yet, the country’s multiparty democratic system remains challenged by a strong authoritarianism that hampers open deliberation in political public discourse.This paper discusses some reasons for this democratic hold-up in Mozambique’s political and social transition within the broad and ongoing democratisation process in Sub-Saharan Africa. With an emphasis on the analysis of the political situation in the northern town of Angoche, this article argues that the persistence of central government authoritarianism is a reminder of a political liberalisation without democratising the political systems. Indeed, local municipal officials are now elected and receive revenue transfers, but remain limited by other measures.2 The central state successfully resists attempts to devolve broader decision-making authority to municipalities. Far from the ideal Weberian type of state bureaucracy, public administration is highly politicised in the sense that the building up of the administrative capacities of the state are seen as a way of consolidating the political leverage of the ruling party – Frelimo. The paper defends, however, that indeed, a detailed analysis of the public political actions at local level, between distinct political structures, shows that successive authoritarian regimes have not totally erased the freedom of speech and thought, even if they have relegated opposition to ever more marginal spaces.